Testing an integrative theoretical model of knowledge-sharing behavior in the context of Wikipedia - CHO, Hichang (Institutional Knowledge at Singapore Management University, 2010)
This study explores how and why people participate in collaborative knowledge-building practices in the context of Wikipedia. Based on a survey of 223 Wikipedians, this study examines the relationship between motivations, internal cognitive beliefs, social-relational factors, and knowledge-sharing intentions. Results from structural equation modeling (SEM) analysis reveal that attitudes, knowledge self-efficacy, and a basic norm of generalized reciprocity have significant and direct relationships with knowledge-sharing intentions. Altruism (an intrinsic motivator) is positively related to attitudes toward knowledge sharing, whereas reputation (an extrinsic motivator) is not a significant predictor of attitude. The study also reveals that a social-relational factor, namely a sense of belonging, is related to knowledge-sharing intentions indirectly through different motivational and social factors such as altruism, subjective norms, knowledge self-efficacy, and generalized reciprocity. Implications for future research and practice are discussed.